Homeostatic plasticity can be induced and expressed to restore synaptic strength at neuromuscular junctions undergoing ALS-related degeneration. (28th July 2017) - Perry, Sarah; Han, Yifu; Das, Anushka; Dickman, Dion
Abstract: Amyotrophic lateral sclerosis (ALS) is debilitating neurodegenerative disease characterized by motor neuron dysfunction and progressive weakening of the neuromuscular junction (NMJ). Hereditary ALS is strongly associated with variants in the human C9orf72 gene. We have characterized C9orf72 pathology at the Drosophila NMJ and utilized several approaches to restore synaptic strength in this model. First, we demonstrate a dramatic reduction in synaptic arborization and active zone number at NMJs following C9orf72 transgenic expression in motor neurons. Further, neurotransmission is similarly reduced at these synapses, consistent with severe degradation. However, despite these defects, C9orf72 synapses still retain the ability to express presynaptic homeostatic plasticity, a fundamental and adaptive form of NMJ plasticity in which perturbation to postsynaptic neurotransmitter receptors leads to a retrograde enhancement in presynaptic release. Next, we show that these endogenous but dormant homeostatic mechanisms can be harnessed to restore synaptic strength despite C9orf72 pathogenesis. Finally, activation of regenerative signaling is not neuroprotective in motor neurons undergoing C9orf72 toxicity. Together, these experiments define synaptic dysfunction at NMJs experiencing ALS-related degradation and demonstrate the potential to activate latent plasticity as a novel therapeutic strategy to restore synaptic strength.